Autogeneration Social Media Content (TikTok, Instagram, Facebook, Twitter) Based On AI & RPA - Fauziah, Jihan Luthfia; Hanifah, Harul Fadiya Baiti; Sujatmoko, Kris (Universitas Telkom, 2025)
Robotic Process Automation (RPA) is an automation solution for creating content on social media. This RPA technology can imitate human behavior. This process is assisted by Artificial Intelligence (AI) to help produce video content using AI tools. Activities such as determining content topics, creating videos, saving videos and uploading them are done automatically. So that the resulting content can be maximized in its publication, it is necessary to determine a topic that can help it. Social media has trending topics which, if turned into content, can have an effect on increasing views, because the content can be more easily found by people who are interested in the content and motivate them to interact. Automatic content creation according to trending topics can be assisted through web scaping. Web scraping is a technique for getting information from websites automatically without having to copy it manually using Python. The implementation of web scraping is in the form of searching for topics that are trending on the Facebook platform.